Performance Enhancement of CPV Systems Using Hybrid PCM-Nanoparticle Cooling and Thermoelectric Generator Integration - Barena, Meiwa; Syalsabila, Jihan; Rusdianasari (International Journal of Mechanics, Energy Engineering and Applied Science (IJMEAS), 2026)
Solar photovoltaic (PV) systems are rapidly being employed as a sustainable energy option, although their efficiency remains highly reliant on operating temperature and surface conditions. High heat accumulation and dust deposits are significant factors in reducing energy conversion efficiency, resulting in lower power output and a shorter module life. To overcome these issues, this study provides an improved solar energy collection strategy that combines light concentration helped by reflectors with an integrated cooling technique based on phase change materials (PCM) and thermoelectric energy recovery. The technology is intended to minimize cell temperature while also limiting efficiency losses caused by environmental exposure and capturing excess heat energy that would otherwise be lost. The evaluation focused on temperature behaviour, electrical output enhancement, and the impact of dust under various working scenarios. The results reveal that PCM integration considerably helps to stabilise panel temperature, whereas the inclusion of a larger surface area increases heat cooling more effectively. When dust is present, performance suffers dramatically, emphasising the significance of surface cleaning and cooling measures. Overall, this integrated system produces more power than typical PV modules, making it more efficient and reliable for long-term use. This approach emphasises the possibility of hybrid passive-active cooling solutions and dust reduction to aid in the application of sustainable solar technology in real-world situations.